O 'conceito' de paradoxo (constantemente referido a Hegel): fé, história e linguagem em S. Kierkegaard - Amaral, Ilana Viana do (2008)
This present research investigates the concept of paradox in S.A. Kierkegaard´s work, starting from the critical dialogue present in the kierkegaardian apprehension of Hegel´s philosophical effort. This investigation searches to show the connections presented in the concept of paradox between faith, language and history, having as a background Kierkegaard´s dialogue with the hegelian categories. Considering that the center of Kierkegaard´s theorical opposition to Hegel is a critique to historical freedom´s formalization from objectivist criterions, we intend to explicit, by means of Hegel and Kierkegaard´s dialogue with Hans Georg Hamann, that the language´s apprehension is an experience of freedom´s exteriorization. The starting point of this Kierkegaard´s opposition is grounded in a lecture incompatible with an objectivation turned out to be autonomous, whose historical-referencial element is the State: this starting point will show itself nucleated in the spirit´s distinct apprehensions realized by both authors